PENGARUH STRUKTUR ASET DAN LIKUIDITAS TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di BEI Periode 2019-2021) - Cahyadewi, Dina Anggun; Prajanto, Agung (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to obtain empirical evidence regarding the effect of asset structure and liquidity on capital structure mediated by profitability. This study has a population of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Purposive sampling is used to determine the sample and 118 samples were obtained. The data source used is secondary data, and the data obtained is then processed using the SPSS (Statistical Product and Service Solution) application tool. This analysis includes path analysis using Sobel tests. The research results stated that asset structure affects profitability. Asset structure, liquidity and profitability affect the capital structure. Profitability mediates the effect of asset structure on capital structure. While Liquidity does not affect profitability. Profitability does not mediate the effect of liquidity on capital structure.